Simulating retrofit incentives and distributional effects of four tenancy law policies: A model analysis using concrete buildings and retrofit options within the German regulatory context - Leo Florian Reutter; Bernadetta Winiewska (Philipps-University Marburg, School of Business and Economics, 2025)
Due to rent control, the primary landlord-tenant dilemma prevents landlords from recovering costs of energy-efficiency retrofits, which mainly benefit tenants. This necessitates tenancy law to allocate retrofit and energy costs adequately. We analyze the impact of Germany's current system and three reform options on both parties' finances using simulations across various building sizes and retrofit ambitions. We find that, in general, investment costs exceed energy savings. Only two of the reform options consistently incentivize landlord investment, albeit at tenants' expense, while the status quo system and the third reform option almost always incentivize landlords to forego retrofits. A sensitivity analysis shows these systems' effectiveness is barely affected by the details of German general tenancy law and local rent markets' characteristics (rent levels and their inflation, valuation of energy efficiency). Designing landlords' retrofit premia to depend on the technically estimated energy demand cost savings is especially promising, contingent on reliable energy performance data.
Keywords: 330; Landlord-tenant dilemma; Tenancy law; Allocation of retrofit and energy costs; Simulation model